Village Guards System of the Ottoman Empire: Employment of Honorary Zaptiyes in Monastir Province - Köseoğlu, Mehmet (Fırat University, 2025)
After the Treaty of Berlin (1878), the geography of Macedonia, including the provinces of Thessaloniki, Bitola and Kosovo, was wanted to be included in the borders of Greece, Bulgaria and Serbia. Greeks, Serbs and Bulgarians residing in the Macedonian provinces began to fight with each other for the benefit of the churches they were affiliated with and the Balkan countries they supported. The struggles continued sometimes with the competition to open their own churches and schools, and sometimes with the terrorist activities of the gangs they formed. The Ottoman Government made great efforts to eliminate the terrorist activities that dominated the cities of Macedonia. To this end, the government did not refrain from taking various measures in the economic, military, political and religious fields. The measures taken by the Ottoman Empire in the fight against gangs, especially in the military field, are worth researching. In our study, it was aimed to investigate the establishment of Security Commissions and the employment of Honorary Zaptiyes as one of the measures implemented by the Ottoman administrators in the Manastır province to ensure public order in the fight against gangs. For this purpose, although Ottoman Archive documents were mostly used as sources, research works, British consulate reports and yearbooks were also used

Berlin Antlaşması’ndan (1878) sonra özellikle de Selanik, Manastır ve Kosova vilayetlerini kapsayan Makedonya coğrafyası Yunanistan, Bulgaristan ve Sırbistan tarafından sınırlarına dahil edilmek istenmiştir. Makedonya vilayetlerinde ikamet eden Rum, Sırp ve Bulgarlar bağlı oldukları kilise ve destekledikleri Balkan ülkelerinin menfaati için birbirleri ile çatışmaya başlamışlardır. Mücadeleler, kimi zaman kendilerine ait kilise ve mektep açma rekabeti ile kimi zaman ise teşkil ettikleri çetelerin terör faaliyetleri ile devam ettirilmiştir. Osmanlı Hükümeti, Makedonya kentlerine hâkim olan terör faaliyetlerini bertaraf etmek amacıyla yoğun gayretler sarfetmiştir. Hükümet, bu amaçla ekonomik, askeri, siyasi ve dini alanlarda çeşitli tedbirler almaktan geri durmamıştır. Osmanlı’nın çeteler ile mücadelede özellikle de askeri alanda ortaya koymuş olduğu tedbirler araştırmaya değer niteliktedir. Çalışmamızda Osmanlı idarecileri tarafından çeteler ile mücadelede asayişi sağlama hususunda Manastır Vilayeti’nde uygulamaya sokulan tedbirlerden biri olarak Emniyet Komisyonlarının teşkil edilmesi ve Fahri Zaptiyelerinin istihdam edilmesinin araştırılması amaçlanmıştır. Bu amaçla kaynak olarak daha çok Osmanlı Arşiv belgelerinden faydalanılmakla birlikte araştırma eserler, İngiliz konsolosluk raporları ve salnamelere de başvurulmuştur
Osmanlı’nın Köy Korucuları Sistemi Teşebbüsü: Manastır Vilayetinde Fahri Zaptiyelerin İstihdam Edilmesi
Keywords: Late Modern Ottoman History; Yakınçağ Osmanlı Tarihi